2020
DOI: 10.1038/s41598-020-62934-8
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl-carbon chain length of two distinct compounds and derivatives are key determinants of their anti-Acanthamoeba activities

Abstract: the opportunistic pathogen, Acanthamoeba castellanii is the causative agent for the sight threatening infection Acanthamoeba keratitis (AK). it is commonly associated with contact lens wearers, and prevalence is increasing at an alarming rate due to an inadequate preventive strategy to protect the lens from this protist. This problem is compounded by the lack of an effective acanthamoebocide, particularly with cysticidal activity in the contact lens solutions. We have used cytotoxicity assays and a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The significant activity of APC12 against Sb-and Milt-resistant parasites, suggests that it can be used for treatment of leishmaniasis caused by these parasites in clinics. This observed phenomenon from the APC series in this study is pathogen-specific, as a parallel study using the same compounds against the parasitic protist, Acanthamoeba, showed that APC16 was the most active [21]. Studies from elsewhere have also produced mixed results.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The significant activity of APC12 against Sb-and Milt-resistant parasites, suggests that it can be used for treatment of leishmaniasis caused by these parasites in clinics. This observed phenomenon from the APC series in this study is pathogen-specific, as a parallel study using the same compounds against the parasitic protist, Acanthamoeba, showed that APC16 was the most active [21]. Studies from elsewhere have also produced mixed results.…”
Section: Discussionmentioning
confidence: 54%
“…Studies from elsewhere have also produced mixed results. For example, short-and long-chain APCs were most effective in reducing tumour development and against fungal infections, respectively [21][22][23][24][25]. The reason for this is speculative and possibly depends on the pathogen's membrane infrastructure, where membranes with fatty acids with long chains are easily disrupted with complementary APCs.…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades the AK disease has been increased especially in United Kingdom due to the extensive use of contact lens. 88,119 A large number of compounds and drugs have been used for the treatment of AK, but most of them are reported ineffective against cyst forms of Acanthamoeba castellanii. Therefore, Mooney et al, 88 assessed the biological activities of APCs and QACs against Acanthamoeba castellanii.…”
Section: Apcs and Qacsmentioning
confidence: 99%
“…To develop a holistic approach to control AK certain measures should be included to augment pharmacotherapy, for example, by reducing incidence of eye infection by including new compounds with proven efficacies against trophozoites and cysts in cleaning solutions of contact lenses. In this regard, a recent study [83] showed that quaternary ammonium compounds (QACs) are more potent than APCs and had cysticidal activity against matured cysts at IC 50s 19.00 ± 0.03 µg/mL and 15.00 ± 0.06 µg/mL for QAC16, and QAC18, respectively. QAC with 12 alkyl carbon chain (QAC12) increased the biomass of trophozoites, delayed encystation by 96 h, but failed to trigger excystation.…”
Section: Improvements In Existing Drugsmentioning
confidence: 99%